PERANCANGAN BUKU KOMIK PERMAINAN TRADISIONAL DENGAN TEKNIK DIGITAL PAINTING UNTUK ANAK USIA 6-12 TAHUN SEBAGAI UPAYA PELESTARIAN BUDAYA - Darmawan, Sigit Dwiki; Martono, Siswo; Yuan, Dhika (Jurnal Art Nouveau, 2017)
Traditional games, a game that has existed since antiquity, and is one of the many cultures that exist in Indonesia. Traditional game is often used as an activity to fill the spare time in antiquity. However, today traditional games are rarely encountered in many places, due to the declining interest of children today against traditional games. Thus the researchers made a comic book that themed traditional games, remember the children who still love the media of comics in the present day. Data collection techniques that will be used in searching for things related to traditional games are through observation, questionnaires, interviews, literature studies, competitor studies, and documentation. The data obtained will have an important role to the problems that arise on The design of traditional game comic books with digital painting techniques for children aged 6-12 years as an effort to preserve the culture, thus requiring a lot of accurate data so that the results obtained can be accounted for. This data is used to find out the initial concept in traditional game comic book design. The result of the design of traditional game comic books as well as the implementation of the media already contains informative and educative elements about the traditional game being lifted, namely the umper plot and the castles. Based on the keyword concept used that is delightfull. So it is expected to be a medium of entertainment as well as a fun learning media for the target audience, ie children aged 6-12 years.Kata Kunci: Perancangan, Buku komik, Permainan tradisional, Petak umpet, Benteng-bentengan, Delightfull, Digital painting.